Case Report: Enfortumab Vedotin for Metastatic Urothelial Carcinoma: A Case Series on the Clinical and Histopathologic Spectrum of Adverse Cutaneous Reactions From Fatal Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis to Dermal Hypersensitivity Reaction - Viscuse, Paul V.; Marques-Piubelli, Mario L.; Heberton, Meghan M.; Parra, Edwin Roger; Shah, Amishi Y.; Siefker-Radtke, Arlene; Gao, Jianjun; Goswami, Sangeeta; Ivan, Doina; Curry, Jonathan L.; Campbell, Matthew T. (Frontiers in Oncology, 2021)
Enfortumab vedotin is a Nectin-4 directed antibody-drug conjugate approved in metastatic urothelial carcinoma following progression on a platinum-containing chemotherapy and immune checkpoint blockade. On-target dermatologic toxicity may occur from Nectin-4 expression in skin. We highlight a case of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis following enfortumab infusions that was ultimately fatal. The second case describes an erythema multiforme-like rash with interface dermatitis related to enfortumab. Dermatologic findings, immunohistochemistry studies, and immune profiling are detailed. These cases demonstrate the potentially catastrophic outcomes in patients treated with enfortumab. Patients must be monitored for cutaneous toxicities with early involvement of dermatology.